Development of a Tablet-based symbol digit modalities test for reliably assessing information processing speed in patients with stroke. Issue 19 (10th September 2016) - Tung, Li-Chen; Yu, Wan-Hui; Lin, Gong-Hong; Yu, Tzu-Ying; Wu, Chien-Te; Tsai, Chia-Yin; Chou, Willy; Chen, Mei-Hsiang; Hsieh, Ching-Lin
Abstract: Purpose: To develop a Tablet-based Symbol Digit Modalities Test (T-SDMT) and to examine the test–retest reliability and concurrent validity of the T-SDMT in patients with stroke. Methods: The study had two phases. In the first phase, six experts, nine college students and five outpatients participated in the development and testing of the T-SDMT. In the second phase, 52 outpatients were evaluated twice (2 weeks apart) with the T-SDMT and SDMT to examine the test–retest reliability and concurrent validity of the T-SDMT. Results: The T-SDMT was developed via expert input and college student/patient feedback. Regarding test–retest reliability, the practise effects of the T-SDMT and SDMT were both trivial ( d =0.12) but significant ( p ≦0.015). The improvement in the T-SDMT (4.7%) was smaller than that in the SDMT (5.6%). The minimal detectable changes (MDC%) of the T-SDMT and SDMT were 6.7 (22.8%) and 10.3 (32.8%), respectively. The T-SDMT and SDMT were highly correlated with each other at the two time points (Pearson's r =0.90–0.91). Conclusions: The T-SDMT demonstrated good concurrent validity with the SDMT. Because the T-SDMT had a smaller practise effect and less random measurement error (superior test–retest reliability), it is recommended over the SDMT for assessing information processing speed in patients with stroke. Implications for Rehabilitation: The Symbol Digit Modalities Test (SDMT), a common measure of information processing speed, showed a substantial practise effect and considerable random measurement error in patients with stroke. The Tablet-based SDMT (T-SDMT) has been developed to reduce the practise effect and random measurement error of the SDMT in patients with stroke. The T-SDMT had smaller practise effect and random measurement error than the SDMT, which can provide more reliable assessments of information processing speed.